Storytelling: Performance, Presentations and Sacral Communication - Zoltán Bódis (Journal of Ethnology and Folkloristics)
Various schools of tale research manifested the relationship of tales of the sacred based on their ideological preconceptions: the relationship between tales and the sacred is refused or accepted. In this article tales are investigated not from the perspective of the possible sacral referent(s) but rather it looks at them as a kind of communicational subsystem that is part of human culture. The focus is on revealing the specific features of sacral communication in the communication system of tales. Sacral communication is a special form of communication in which the elements of the communication model are transformed. The goal of sacral communication is exactly this kind of identity creation. This may be oriented towards creating a personal or a communal self-identity. Among its characteristics we may find the special type of language forms in which the predominance of linguistic elements pushes the sense conveying possibilities more into the background than usual, and those linguistic forms that restructure consciousness become emphasized. In this communication the tale telling is transformed by a language use characteristic of sacral communication (rhythm, repetition and rhetorical forms). Various examples explain that traditional tale telling creates a complex effect related to the visual, auditory, and kinetic senses: a modification and transformation of the self-understanding and self-identity that connect the world of tale telling to sacral communication.